Issues of Ensuring the Economic Security of the Northern Regions of Russia - BOGOMOLOVA, Lubov; USTYUZHANTSEVA, Anastasiya (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This paper presents the results of research of the current economic security in the northern region of Russia. The paper covers the influence of the National Technological Initiative system of Russia on economic security in the Khanty-Mansi Autonomous Okrug – Ugra. The main aim of the study is to explore the issues and prospects for ensuring economic security in the northern oil-and-gas producing regions of Russia as a course of priority of the policy of the government in the northern region. The authors conducted a system analysis and assessed the scientific and technical, technological, and innovative objectives of the regional economic development.RESUMEN Este artículo presenta los resultados de la investigación de la seguridad económica actual en la región norte de Rusia. El documento cubre la influencia del sistema de Iniciativa Tecnológica Nacional de Rusia sobre la seguridad económica en el Okrug Autónomo Khanty-Mansi - Ugra. El objetivo principal del estudio es explorar los problemas y las perspectivas para garantizar la seguridad económica en las regiones productoras de petróleo y gas del norte de Rusia como un curso prioritario de la política del gobierno en la región norte. Los autores realizaron un análisis del sistema y evaluaron los objetivos científicos y técnicos, tecnológicos e innovadores del desarrollo económico regional.